Determinants of Financial Distress of Transportation Companies Listed on the Indonesia Stock Exchange (2015-2021) - Hicca Maria Gandi Putri Aruan; Manatap Berliana Lumbangaol; Rizki Christian Sipayung (SEAN Institute, 2024)
This study aims to determine and analyse the effect of return on equity, current ratio, total asset turnover, dividend payout ratio and sales growth on financial distress. The population in the study were transportation companies listed on the Indonesia Stock Exchange from 2015 to 2021, totalling 54 companies. The sample in this study was determined using the criterian purposive sampling approach, and obtained a sample size of 13 companies. The data used in this study are secondary timeseries cross section data. The data was collected using the documentation study method. The data collected in this study were analysed using quantitative methods, which include: descriptive statistical analysis, classical assumption test, and multiple linear regression analysis. This study concluded that: return on equity and current ratio have a significant negative effect on financial distress, while total asset turnover, divident payout ratio and sales growth have a significant positive effect on financial distress.